DETERMINAN YANG MEMPENGARUHI IMUNISASI PENTAVALEN LANJUTAN - Meliyanti, Fera; Heryanto, Eko (Jurnal Kesehatan dan Pembangunan, 2025)
To maintain an optimal level of immunity, follow-up immunization is required. Follow-up immunization is a repeat of basic immunization to extend the protection period of children who have received basic immunization. The use of pentavalent immunization (DPT-HB-HIB) for infant and toddler immunization was launched in 2014 by the Indonesian Ministry of Health. Indonesian children will be better protected from the threat of immunization-preventable diseases (PD3I), with the addition of Haemophilus influenzae type b (Hib) vaccine given together with DPT and Hepatitis B vaccines. This Indonesian-made combination tetravalent (DPT-HB) vaccine development vaccine is called Pentavalent, because it is a combination of 5 antigens, namely DPT (Diphtheria, Pertussis and Tetanus), Hepatitis B, and HiB. This study aims to determine the determinants that affect the completeness of continued pentavalent immunization. This study is a quantitative study using a cross sectional approach. The population in this study were children aged 18-24 months in the work area of UPTD Puskesmas Tanjung Baru from January to March 2022 totaling 405 with a sample of 80 children aged 18-24 months. The results showed that there was a significant relationship between maternal education and the completeness of advanced pentavalent immunization with a p-value of 0.004, there was a significant relationship between maternal knowledge and the completeness of advanced pentavalent immunization with a p-value of 0.021, there was a significant relationship between maternal attitudes and the completeness of advanced pentavalent immunization with a p-value of 0.009 and there was a significant relationship between family support and the completeness of advanced pentavalent immunization with a p-value of 0.012. From the results of this study, it is hoped that health workers, especially mother and child health (KIA) program holders, can pay special attention to mothers in providing counseling on advanced pentavalent immunization